Hubungan Kebisingan dengan Keluhan Siswa SD di Nagari Nanggalo Kecamatan Koto XI Tarusan Tahun 2023 - Atmadio, Rahmadilla Putri; Irfan, Asep; Hidayanti, Rahmi; Mahaza, Mahaza; Onasis, Aidil (Jurnal Kesehatan Lingkungan Mandiri, 2025)
Noise is an unwanted sound. Noise in the school environment can have negative effects on students, such as difficulty concentrating, fatigue during learning, discomfort, and communication disturbances. This study aimed to determine the relationship between noise and student complaints at elementary schools (SD) in Nagari Nanggalo, Koto XI Tarusan District, in 2023. This research used an observational analytic design. The population consisted of all students from three elementary schools in Nagari Nanggalo, totaling 443 students. Noise measurements were taken at 8 points, and the student sample consisted of 82 students. Data were collected by measuring noise levels using a Sound Level Meter and a stopwatch, as well as through direct interviews using a questionnaire. Data analysis was conducted using univariate and bivariate methods with the Chi-Square statistical test. The results showed that five of the measured points had noise levels exceeding the environmental health quality standards. A total of 26 students (31.7%) reported complaints, primarily related to difficulty concentrating and disturbances in communication during learning. The study found a significant relationship between noise and student complaints (p=0.001), indicating that noise in the school environment in Nagari Nanggalo is significantly associated with student complaints, such as difficulty concentrating and communication disturbances, with most noise levels exceeding the standard threshold.